(untitled) (Research, Society and Development, 2023)
Cerebral palsy, a neuromotor condition resulting from damage or abnormal brain development in childhood, directly impacts motor skills and often affects emotional and social aspects. The aim of this study is to comprehensively explore the various aspects of cerebral palsy and evaluate the effectiveness of equine therapy as a promising therapeutic intervention. Using an Integrative Literature Review methodology, the research sought evidence regarding the efficacy of equine therapy in treating cerebral palsy. The results indicate that therapeutic interventions such as equine therapy, play, intensive body weight support treatment, PediaSuit protocol, and virtual reality have positive impacts on the lives of children and adolescents with cerebral palsy. The final considerations consistently highlight the significant benefits of equine therapy in treatment, demonstrating improvements not only in functional changes but also in the social and emotional aspects of patients.